Separation of crude oil emulsion via ultrasonic technology - Siti Zaleha, Abdullah (2009)
Emulsions have long been of great practical interest due to their widespread occurrence in everyday life. They may be found in important areas such as food, cosmetic, pharmaceutical and agricultural industry. Emulsions are also found in the petroleum industry. Water separated from water in oil emulsion by various method such as ultrasonic, chemical or microwave demulsification. Emulsifier are surfactant used to develop high surface pressure at emulsion interface. In this research the ultrasonic technology used to break the water in oil emulsion. For stability part, about three type of crude oil used in the stability part which are include heavy and light crude oil. The emulsion prepared by mix the crude oil with the emulsifier such as Span 80.Tween 80 and SDDS and the propeller will used to mix the mixture vigorously for 5 minute. The next step pour some water slowly into the crude oil and wait until 10 minutes to ensure the mixture is completely mixing.The speed for propeller is about 1250rpm.the sample will check water in oil emulsion by filter paper or test tube test.Record the data and observed what happen occur during experiment. For the demulsification part the Masila crude oil will used to compare the ultrasonic with chemical demulsification method. The hexylamine is the chemical used to break the emulsion.The data and observation will be record and graph will be plotted to show which one give best performance to break the emulsion.In conclusion the ultrasonic is not effienct method to break the emulsion compared to the chemical method.